Adjective-Noun Collocations in the Batak Toba Language: A Cognitive Semantic Analysis - Beslina Afriani Siagian; Nurhayati Sitorus (Leksema: Jurnal Bahasa dan Sastra, 2026)
While collocation research has been approached from various semantic viewpoints, it has yet to thoroughly explore the intricate meaning relationships between words within collocations. This study investigates adjective-noun collocations in the Batak Toba language through cognitive semantic analysis. By employing cognitive semantics, the study explores the meanings of nouns and adjectives in relation to frames, domains, and conceptual blending. Song lyrics serve as the data source for analysis, providing a rich and culturally significant context for examining language use. Employing domain theory, frame theory, and conceptual integration theory, the data underwent rigorous examination. The results indicate that noun and adjective collocations are formed based on the compatibility between the noun and the adjective. The characteristics of collocations, for both nouns and adjectives, can be interpreted from the combinations of symbols that arise from phonological sequences within the constructional scheme. This research identifies three types of collocations: compositional collocations, limited compositional collocations, and non-compositional collocations. Furthermore, semantic frames shed light on the cultural beliefs embedded within the meanings of collocations in Batak Toba. These frames reveal how cultural contexts influence the interpretation and usage of collocations, demonstrating the intricate connection between language and culture. Moreover, conceptual integration clarifies the process of collocation formation and meaning through the interaction of input space 1, input space 2, generic space, and blended space. This interaction highlights the dynamic and creative aspects of language use among Batak Toba speakers. The study finds that speakers of the Batak Toba language demonstrate strong cognitive abilities in creating collocations, showcasing their linguistic creativity and cognitive flexibility. This research not only contributes to the understanding of collocation in the Batak Toba language but also underscores the importance of cognitive semantics in uncovering the deeper meaning relationships in language.